Drosophila Fos mediates ERK and JNK signals via distinct phosphorylation sites. - Ciapponi, L.; Jackson, D.B.; Mlodzik, M.; Bohmann, D. (Genes & Development, 2001)
During Drosophila development Fos acts downstream from the JNK pathway. Here we show that it can also mediate ERK signaling in wing vein formation and photoreceptor differentiation. Drosophila JNK and ERK phosphorylate D-Fos with overlapping, but distinct, patterns. Analysis of flies expressing phosphorylation site point mutants of D-Fos revealed that the transcription factor responds differentially to JNK and ERK signals. Mutations in the phosphorylation sites for JNK interfere specifically with the biological effects of JNK activation, whereas mutations in ERK phosphorylation sites affect responses to the EGF receptor-Ras-ERK pathway. These results indicate that the distinction between ERK and JNK signals can be made at the level of D-Fos, and that different pathway-specific phosphorylated forms of the protein can elicit different responses.